An Investigation of the Effect of Different Nanofluids in a Solar Collector - Fakhim, H. A. (Engineering, Technology & Applied Science Research, 2017)
In this article, we examine the use of different nanofluids in a solar collector in a parabolic form. Temperature, thermal efficiency and outlet average temperature for a conventional parabolic collector and a collector with nanofluid are compared. The effect of various parameters (concentration ratio, volume fraction of nanoparticles, absorption and fluid velocity) are studied. Results are discussed and it is shown that nano fluid increases the efficiency of the collector.